MART-10, the vitamin D analog, is a potent drug to inhibit anaplastic thyroid cancer cell metastatic potential. Issue 1 (1st December 2015) - Chiang, Kun-Chun; Kuo, Sheng-Fong; Chen, Chih-Hung; Ng, Sohching; Lin, Shu-Fu; Yeh, Chun-Nan; Chen, Li-Wei; Takano, Masashi; Chen, Tai C.; Juang, Horng-Heng; Kittaka, Atsushi; Lin, Jen-Der; et al.
Highlights Anaplastic thyroid cancer is a very aggressive disease without effective treatment available. MART-10 MART-10 has been shown to be more pottent than 1α, 25(OH)2D3 in inhibitin a variety of cancers growth. MART-10 and 1α, 25(OH)2D3 both are effitve drug to inhibt anaplastic thyroid cancer metasasis with MART-10 much more poten, encouraging further in vivo studies.